Pengaruh Partisipasi Anggota terhadap Kinerja KUD Di Kecamatan Tapung Kabupaten Kampar - risman, risman (Komunitas Manajemen Kompetitif, 2015)
Abstract: The issue of performance KUD in Kampar regency low because alleged by the participation of its members. Based on the results of studies using 93 respondents KUD members proves that the participation of members and not significant positive effect on the performance of cooperatives, it can be shown with the sig of 0.034 and the value of the effect of 0.008. Value influence member participation, and not significant positive effect on the performance of KUD members. This means KUD is not yet a true KUD, where KUD good steward is to be memintarkan and prosper member, go look for life or property at KUD. Keywords: KUD Performance, Member Participation